Determinants factor of housing loan/house financing pricing: comparative evaluation between conventional and Islamic Bank in Malaysia. - Noorul Hafizah, Hashim; Mutia Sobihah, Abd Halim (2014)
The demand for house in Malaysia is increase due to the increasing of population and their life style. Furthermore, buying a house is one of the methods of long term investment. Due to that, financial institutions in Malaysia was competing each other in offering housing loan/house financing to the customer. Financial systems in Malaysia has divided into two major systems which is Conventional and Islamic system, so, this financing also divided into two which are housing loan for conventional and house financing in Islamic. Thus, the purpose of this study is to investigate the factors considered by banks in determining housing loan/house financing price; whereby a comparative evaluation will conduct between Conventional Bank and Islamic Bank. Net interest margin is using as a proxy to housing loan/house financing interest rate. To achieve the objective, this study employs the convergent interview and regression of the model. Software of Statistical Package for Social Science (SPSS) version 20 will be used as analysis technique to analyzed data.